Identification of Zika virus in immature phases of Aedes aegypti and Aedes albopictus: a surveillance strategy for outbreak anticipation - Maniero,V.C. (2019)
A progressive increase in the circulation of arboviruses in tropical countries has been observed, accounting for 700,000 yearly deaths in the world. The main objective of this article was to identify the presence of Zika (ZIKV), dengue (DENV), and Chikungunya (CHIKV) viruses in immature stages of Aedes aegypti and Ae. albopictus. Household collections of immature phases of the vectors were carried out in the years 2015 and 2016. A total of 2902 dwellings were visited and the rate of infestation with larvae and pupae of Aedes mosquitoes was 283/1462 (19.4%) in March 2015 and 55/1440 (3.8%) in June 2015. In March 2015, 907 larvae/pupae were collected (583 or 64.3% of Ae. aegypti and 324 or 35.7% of Ae. albopictus) while in June 2015 there was a reduction in the number of immature forms found: 197 larvae/pupae (121 or 61.4% of Ae. aegypti and 76 or 38.6% of Ae. albopictus). This reduction was accompanied by a decrease in suspected human ZIKV cases from March to June 2015. The RT-qPCR performed in 18 pools identified that three (two of Ae. aegypti and one of Ae. albopictus) were positive for ZIKV, and none were positive for DENV or CHIKV. Our findings demonstrated that ZIKV was present in immature stages of insect vectors in the study region at least five months prior to the peak of ZIKV associated cases. Xenomonitoring of immature phases of the vectors may prove useful for predicting outbreaks.